Analysis of the proposal for the EU Artificial Intelligence Act - Melenová, Markéta; Kliegr, Tomáš; Vadinský, Ondřej; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2023)
This work attempted to explore the new landscape of proposed EU Artificial Intelligence act. For this the feedback submitted by general public was collected and analysed using semi-automated approach. Agglomerative clustering was used to identify the types of feedbacks. Neverheless, when used and tested in a standard way, such model assigned a feedback document, which typically covered whole range of topics, to only one cluster. Due to this, it was impossible to interpret, what topic characterizes given cluster or verify manually if the assignment is correct. In order to overcome the problem of clustering that assigns the whole document to 1 cluster only, to get a more detailed granularity, I decided to split the feedback files to smaller chunks based on an approximate paragraph pattern. This approach enhances the selected model’s suitability for the purposes of deeper analysis of selected topics, if needed, mapping the main topics of feedback to individual AIA articles and reflecting on the manner how the feedback was reflected in the final AIA version. This approach is characterised by high level of interpretability together with relatively low number of documents in the training set, which makes it possible to identify any misattributions in manual review without much time or effort spent. This is one of the by-products of the thesis. The work provides an overview of the main types of feedback and answers the research question if the processing of individual thematic parts of the EU Artificial Intelligence Act proposal aligns with the extent of feedback submitted during the designated feedback period.
Vedoucí práce: Tomáš Kliegr
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: kognitivní informatika [obor dipl. práce]; diplomové práce; master's theses